Existence of three positive solutions for boundary value problem with fractional order and infinite delay - Benaouda Hedia (Annals of the West University of Timisoara: Mathematics and Computer Science, 2015)
In this paper we investigate the existence three positives solutions by using Leggett-Williams fixed point theorem in cones for three boundary value problem with fractional order and infinite delay.